Evaluation of DNA, BSA binding, and antimicrobial activity of new synthesized neodymium complex containing 29-dimethyl 110-phenanthroline. Issue 3 (17th February 2018) - Moradi, Zohreh; Khorasani-Motlagh, Mozhgan; Rezvani, Ali Reza; Noroozifar, Meissam
Abstract : In order to evaluate biological potential of a novel synthesized complex [Nd(dmp)2 Cl3 .OH2 ] where dmp is 29-dimethyl 110-phenanthroline, the DNA-binding, cleavage, BSA binding, and antimicrobial activity properties of the complex are investigated by multispectroscopic techniques study in physiological buffer (pH 7.2).The intrinsic binding constant ( K b ) for interaction of Nd(III) complex and FS–DNA is calculated by UV–Vis ( K b = 2.7 ± 0.07 × 10 5 ) and fluorescence spectroscopy ( K b = 1.13 ± 0.03 × 10 5 ). The Stern–Volmer constant ( K SV ), thermodynamic parameters including free energy change (Δ G °), enthalpy change ( ∆H °), and entropy change ( ∆S °), are calculated by fluorescent data and Vant' Hoff equation. The experimental results show that the complex can bind to FS–DNA and the major binding mode is groove binding. Meanwhile, the interaction of Nd(III) complex with protein, bovine serum albumin (BSA), has also been studied by using absorption and emission spectroscopic tools. The experimental results show that the complex exhibits good binding propensity to BSA. The positive Δ H ° and ∆S ° values indicate that the hydrophobic interaction is main force in the binding of the Nd(III) complex to BSA, and the complex can quench the intrinsic fluorescence of BSA remarkably through a static quenching process. Also, DNA cleavage was investigated by agarose gel electrophoresis that according to the results cleavage of DNA increased with increasing of concentration of the complex. Antimicrobial screening test gives good results in the presence of Nd(III) complex system.